2019
DOI: 10.1002/pi.5928
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic behaviour of self‐assembling polyurethane and poly(vinyl alcohol)

Abstract: The rheological behaviour of polyurethane (PU) and poly(vinyl alcohol) (PVA) was investigated in aqueous solution and the hydrogel state. The dependence of viscosity on polymer concentration is discussed. The formation of supramolecular structures induced by temperature increase or shear conditions was evidenced. In PU solutions, as temperature increases, a self‐assembling process occurs due to hydrogen bonding and hydrophobic interactions determining a thermoreversible hydrogel formation. In creep and recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…The rheological behaviour of PVA was investigated in an aqueous solution and in the hydrogel state. Bercea et al [27] found that in PVA solutions, shear-induced aggregation at 37 • C and PVA hydrogels present a high elasticity and stability due to the strong polymer-polymer interactions established between the polymer chains. According to those authors, PVA/polyurethane composite hydrogel presents high elasticity up to shear stress of 3 MPa, being followed by a rapid recovery of the hydrogel structure after showing successive levels of deformation.…”
Section: Introductionmentioning
confidence: 99%
“…The rheological behaviour of PVA was investigated in an aqueous solution and in the hydrogel state. Bercea et al [27] found that in PVA solutions, shear-induced aggregation at 37 • C and PVA hydrogels present a high elasticity and stability due to the strong polymer-polymer interactions established between the polymer chains. According to those authors, PVA/polyurethane composite hydrogel presents high elasticity up to shear stress of 3 MPa, being followed by a rapid recovery of the hydrogel structure after showing successive levels of deformation.…”
Section: Introductionmentioning
confidence: 99%
“…WPU solution and PVA were used as a cross‐linking agent in the progress of synthesizing waterborne polyurethane hydrogels, which confirmed that WPU and PVA formed a homogeneous miscible system through hydrogen bonds 14 . The viscosity behavior of PU and PVA aqueous solutions and the mixture of different compositions at 37°C were discussed 15 . The preparation of WPU/PVA composites could be divided into two methods: electrospinning and solution blending.…”
Section: Introductionmentioning
confidence: 83%
“…The direct comparison of the linkers in A and B strongly suggests that the Thorpe-Ingold effect induced by the gemdimethyl unit is crucial for the supramolecular polymerization, thus indicating that indeed a ring-chain transformation is occurring. Next to the system described by Sijbesma and Meijer, other compounds have been described that influence the viscosity by dynamic supramolecular interactions, also leading to a viscosity increase at elevated temperatures [16][17][18].…”
Section: Introductionmentioning
confidence: 99%